2020
DOI: 10.21203/rs.3.rs-34221/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Sagittal Profile and Radiographic Parameters in Symptomatic Thoracolumbar Disc Herniation Patients

Abstract: Background Few studies describe thoracolumbar disc herniation (TLDH) as an isolated category, it is frequently classified as the lower thoracic spine or upper lumbar spine. Thus, less is known about the morphology and aetiology of TLDH compared to lumbar disc herniation (LDH)The aim of study is to investigate sagittal alignment in TLDH, and analyze sagittal profile with radiographic parameters.Methods Data from 70 patients diagnosed with TLDH were retrospectively reviewed. The thoracic-lumbar alignment was dep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Lumbar disc herniation (LDH) is one of the main degenerative spinal diseases, which often occurs in the elderly population [6]. Recently, studies have investigated the characteristics of the sagittal pro les in patients with disc herniation [7,8], and a at back with lower lumbar lordosis, lower pelvic incidence and greater vertical orientation has been reported to be a risk factor for disc herniation [9]. Nevertheless, the sample size in those studies is relatively small and they were mainly concentrated in adolescents, the middle-aged population, and somewhat older population with a maximum average age of 63.5 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar disc herniation (LDH) is one of the main degenerative spinal diseases, which often occurs in the elderly population [6]. Recently, studies have investigated the characteristics of the sagittal pro les in patients with disc herniation [7,8], and a at back with lower lumbar lordosis, lower pelvic incidence and greater vertical orientation has been reported to be a risk factor for disc herniation [9]. Nevertheless, the sample size in those studies is relatively small and they were mainly concentrated in adolescents, the middle-aged population, and somewhat older population with a maximum average age of 63.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, few studies have been carried out to determine the relationship between different Roussouly types of the spine and lumbar disc herniation (LDH) in the elderly Chinese patients. Previous studies also demonstrated that patients with different spinal pro les tended to bear disc herniation in different lumbar segments [7,9,10]. However, the details remain lacking and more studies are necessary to be investigated.…”
Section: Introductionmentioning
confidence: 99%